Catalytic pyrolysis of pinewood using metal oxide catalysts in an integrated reactor system. Issue 5 (3rd September 2017) - Guda, Vamshi Krishna; Toghiani, Hossein
ABSTRACT: Catalytic fast pyrolysis is a technology that has been widely explored in the past decade for direct conversion of solid biomass to partially upgraded bio-oil containing hydrocarbons. Zeolites, both unpromoted and promoted with metal ions, have been the most widely studied catalysts. As the yield and composition of the bio-oils from catalytic pyrolysis are a function of the catalyst employed, exploring catalyst compositions other than zeolites is necessary. Our study explored metal oxide catalysts, including sulfated zirconia, tungstated zirconia, zirconia-titania and titania (anatase and rutile), for catalyzing pinewood pyrolysis vapors; pyrolysis was carried out at 450 °C, while the catalysis was performed at 425 °C, at a weight hourly space velocity of 14 h − 1 . The liquid, solid (char) and gas yields varied from 36.3 to 45.2%, 15.6 to 17% and 44.3 to 37.7%, respectively. The characterization of the catalyzed bio-oils showed that the most effective, among the tested catalysts, for catalyzing the pinewood pyrolysis vapors to produce partially deoxygenated bio-oils was sulfated zirconia catalyst with bio-oil yields of 39.5%. Sulfated zirconia catalyzed bio-oil possessed 33% lower oxygen content, 56% higher heating value (HHV), and 51% lower acid value compared to uncatalyzed bio-oil. Titania catalysts favored higher bio-oil yields, with titania-rutile and titania-anatase resulting in 43% and 45% bio-oil yield, respectively.